1998
DOI: 10.1357/002224098321822384
|View full text |Cite
|
Sign up to set email alerts
|

A numerical study of layer formation due to fingers in double-diffusive convection in a vertically-bounded domain

Abstract: The evolution of ngers in a double-diffusivesystem is investigatedusing numerical integration of two-dimensional equations of motion for an incompressible, Boussinesq uid. The computational domain is periodic in the horizontal direction and is closed with no-ux boundary conditions in the vertical direction. The main result of this study is the evolution of the system from initially linear pro les for both fast and slow diffusing components to a layered state characterized by a nger zone sandwiched between two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…18 These blobs also play an important role in fingers reaching a finite amplitude, when blobs regularly detach from the tips of the fingers, keeping the extent of the finger zone at a statistically steady state. 3,9 The present simulations have not reached an equilibrium state ͑e.g., Fig. 4͒ and do not display any blob-shedding during the simulation period.…”
Section: A Growth Of Fingersmentioning
confidence: 64%
See 2 more Smart Citations
“…18 These blobs also play an important role in fingers reaching a finite amplitude, when blobs regularly detach from the tips of the fingers, keeping the extent of the finger zone at a statistically steady state. 3,9 The present simulations have not reached an equilibrium state ͑e.g., Fig. 4͒ and do not display any blob-shedding during the simulation period.…”
Section: A Growth Of Fingersmentioning
confidence: 64%
“…We have only focused on the initial evolution of the fingers, with special emphasis on the structure of the individual fingers. The investigation of the finite amplitude behavior of the system consisting of mixed layers and finger interfaces requires a significantly larger domain and a longer integration period ͑e.g., Ö zgökmen et al 9 ͒.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…For fingering convection there is not enough experimental evidence to give a clear‐cut answer. The numerical simulations of Shen [20] and Özgökmen et al [22] suggest that the “four‐thirds” law is valid, but it fails if applied to the oceanic observations of the C‐SALT campaign [26], [12].…”
Section: Vertical Fluxesmentioning
confidence: 99%
“…While their fingers grow all the way across the small computational domain, they also induce larger scale recirculation cells in the streamfunction field. Finally, Özgökmen et al [22] have shown a simulation that initially uses linear profiles of temperature and salinity. They report the emergence of convective cells close to the upper and lower boundary that eventually grow, sandwiching a high gradient zone between them.…”
Section: Introductionmentioning
confidence: 99%